Producing research, training, health, and education in the teaching-service-community integration - Bravo, Victória Ângela Adami [UNESP]; Dos Santos, Lucas Cardoso [UNESP]; Cyrino, Eliana Goldfarb [UNESP]; Cyrino, Antônio de Pádua Pithon [UNESP]; Villardi, Marina Lemos; Pinto, Tiago Rocha (FapUNIFESP (SciELO), 2018)
The present study is an experience report about the development of research, knowledge production, and training in the interface between university and health services, based on the Pró-Ensino na Saúde program (Capes public notice no. 24/2010). It presents problem-solving education, interprofessional education, permanent education of healthcare professionals and teachers, and Brazilian Curricular Guidelines as drivers to a professional education committed to the development of the Brazilian National Health System, focused specifically on valuing the integration between public universities and health services. The investigations carried out approached different dimensions of teaching in primary health care involving pedagogical practices, teaching education and development, performance of healthcare professionals as teachers, pedagogical innovations, and questions related to health work practices. A fragility in the organic relationship between university and primary care, and innovations that pace toward rupture with the instituted teaching method were pointed in the richness and diversity of the studies found.
Producción de investigación, formación, salud y educación en la integración enseñanza servicio y comunidad
Produzindo pesquisa, formação, saúde e educação na integração ensino, serviço e comunidade
Keywords: Higher education; Interprofessional relations; Primary health care